Optimal battery sizing considering degradation for renewable energy integration - De-la-Torre-Fazio, Sebastián Bienvenido; González-González, José Manuel; Aguado-Sánchez, José Antonio; Martín-Rivas, Sebastián (Institution of Engineering and Technology (IET), 2019)
The problem of sizing an electrochemical energy storage system for renewable energy integration is a complex task. There are several system input parameters that must be taken into account for a correct design. Among them, the ageing characteristic of the technology, the service that the system provides, i.e. the power profile that the system faces and the desired C-rate are considered. A simple solution for this problem is not available in the literature. This study presents a simple yet robust optimisation-based model for renewable energy integration. The model explicitly takes into account the intrinsic battery ageing process. The authors propose a formulation for the optimisation problem that can be written in terms of just one continuous variable, namely, the amount of energy that the battery is able to store (battery size); using the proposed procedure, solving the problem obtained is a relatively straightforward task. Results are first discussed using an illustrative example and later extended to two real case studies.
Keywords: Aprendizaje automático (Inteligencia artificial); Baterías de acumuladores; Battery sizing; Degradation; Renewable Energy Integration; Optimization